GJG 32 High oil and high yielding Spanish bunch groundnut variety for Gujarat: GJG 32 High oil and high yielding Spanish bunch groundnut variety for Gujarat - K L DOBARIYA; N D DHOLARIYA (Journal of Oilseeds Research, 2020)
A Spanish bunch groundnut variety GJG 32 was evaluated in twenty locations over five years during rainfed kharif seasons of 2011 to 2016. This variety recorded an overall mean pod yield of 3392 kg/ha, which was higher than the check varieties viz., GG 7 (2766 kg/ha), GJG 9 (2765 kg/ha), and TG 37A (2816 kg/ha). The variety GJG 32 exhibited 22.61%, 22.64%, and 15.38% increase in pod yield over the check varieties viz., GG 7, GJG 9, and TG 37A, respectively. The kernel yield (2324 kg/ha) of GJG 32 over the check varieties viz., GG 7 (1932 kg/ha), GJG 9 (1983 kg/ha) and TG 37A (1990 kg/ha) was better and higher by 16.86% (GG 7), 14.67% (GJG 9) and 14.37% (TG 37A) over the checks respectively. GJG 32 recorded a mean 100-kernel weight of 35.9g, shelling out-turns of 68.5% and oil content 53.9%. This variety was resistant to tikka and rust diseases as compared to the check varieties whereas; it showed comparable reactions against major diseases. Due to its consistent superior performance over locations and years, GJG 32 has been proposed for release for general cultivation in the rainfed kharif groundnut growing areas Gujarat state.